2010
DOI: 10.1155/2011/875824
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HDAC6 in Cancer

Abstract: Histone deacetylase 6 (HDAC6), a member of the HDAC family whose major substrate is α-tubulin, has become a target for drug development to treat cancer due to its major contribution in oncogenic cell transformation. Overexpression of HDAC6 correlates with tumorigenesis and improved survival; therefore, HDAC6 may be used as a marker for prognosis. Previous work demonstrated that in multiple myeloma cells, inhibition of HDAC6 results in apoptosis. Furthermore, HDAC6 is required for the activation of heat-shock f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
306
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(312 citation statements)
references
References 58 publications
3
306
0
3
Order By: Relevance
“…Because HDAC6 plays a critical role in autophagy activation, we consistently found that knockdown of HDAC6 also enhanced Btz-induced apoptosis by inhibition of autophagy and UPR. Involvement of HDAC6 in aggresome formation and UPRmediated autophagy is well established in many neurodegenerative disease studies and has recently been implicated in chemoresistance (26). Concomitantly, our data also show a critical role for HDAC6 in aggresome formation upon accumulation of unfolded/misfolded proteins followed by the Btz treatment in HNSCC cells.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Because HDAC6 plays a critical role in autophagy activation, we consistently found that knockdown of HDAC6 also enhanced Btz-induced apoptosis by inhibition of autophagy and UPR. Involvement of HDAC6 in aggresome formation and UPRmediated autophagy is well established in many neurodegenerative disease studies and has recently been implicated in chemoresistance (26). Concomitantly, our data also show a critical role for HDAC6 in aggresome formation upon accumulation of unfolded/misfolded proteins followed by the Btz treatment in HNSCC cells.…”
Section: Discussionsupporting
confidence: 77%
“…HDAC6 Is Required for Aggresome Formation and Induction of Autophagy in HNSCC Cells-Recently, it has been shown that HDAC6 was involved in gathering scattered polyubiquitylated CPAs and transporting them to the microtubule organizing center to promote aggresome formation (26,27). To determine whether HDAC6 played a role in Btz-induced aggresome formation and autophagy induction in SCC cells, we stably knocked down HDAC6 using shRNA (HDAC6KD) in SCC1 cells (Fig.…”
Section: Btz Induces Both Autophagy and Apoptosis In Hnscc Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Among the class II proteins, HDAC6 is overexpressed in oral squamous cell carcinoma and breast cancer tumors. 11 Unlike other HDAC isoforms, HDAC6 plays important roles in multiple cancer-relevant biological processes that are not epigenetic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…HDAC6, in particular, has distinct structure features and unique cytoplasmic functions in the regulation of cytoskeleton, cell migration, cell reprogramming and pluripotency [4,5]. Upregulation or activation of HDAC6 has also been implicated in tumorigenesis, neurodegenerative diseases and inflammatory disorders [6,7], implying HDAC6 is a potential therapeutic target for pharmacological intervention strategy. While the list of cytoplasmic acetylated proteins controlled by HDAC6 is rapidly growing, the function of HDAC6 in viral infection is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%